Assessing the Impact of the Covid-19 Pandemic on Publishing Indicators: A Case Study of Iran - Zavaraqi, Rasoul; HajiAsadi, Farinaz (ADA University Library, 2024)
This paper focuses on analyzing the publishing and economic indicators of the Iranian Publishing Industry before, during, and after the COVID-19 pandemic. The study employs a quantitative approach with content analysis methodology, utilizing a researcher-made checklist for data collection. The statistical population consists of 722,988 book titles published in Iran from April 2016 to April 2023, sourced from statistical reports in the Iran Monthly Bank of Book Publishers. Trends in book publication, geographical distribution, and pricing are compared across the three time periods, revealing increases in certain subjects during the pandemic, such as philosophy, social sciences, art, literature, and geography. However, the average number of publications has decreased across all topics during this period. Additionally, other publishing indicators show no significant differences before and after the pandemic, highlighting the industry's resilience despite challenges posed by the global health crisis.
Keywords: Publishing industry; Covid-19 pandemic; Publishing indicators; Cultural progression; Iran's publishing landscape